The sodium transporter encoded by the HKT1;2 gene modulates sodium/potassium homeostasis in tomato shoots under salinity. (20th January 2017) - Jaime‐Pérez, Noelia; Pineda, Benito; García‐Sogo, Begoña; Atares, Alejandro; Athman, Asmini; Byrt, Caitlin S.; Olías, Raquel; Asins, Maria José; Gilliham, Matthew; Moreno, Vicente; Belver, Andrés
Abstract: Excessive soil salinity diminishes crop yield and quality. In a previous study in tomato, we identified two closely linked genes encoding HKT1‐like transporters, HKT1 ; 1 and HKT1 ; 2, as candidate genes for a major quantitative trait locus ( kc7 . 1 ) related to shoot Na + /K + homeostasis – a major salt tolerance trait – using two populations of recombinant inbred lines (RILs). Here, we determine the effectiveness of these genes in conferring improved salt tolerance by using two near‐isogenic lines (NILs) that were homozygous for either the Solanum lycopersicum allele (NIL17) or for the Solanum cheesmaniae allele (NIL14) at both HKT1 loci; transgenic lines derived from these NILs in which each HKT1 ; 1 and HKT1 ; 2 had been silenced by stable transformation were also used. Silencing of ScHKT1 ; 2 and SlHKT1 ; 2 altered the leaf Na + /K + ratio and caused hypersensitivity to salinity in plants cultivated under transpiring conditions, whereas silencing SlHKT1 ; 1 / ScHKT1 ; 1 had a lesser effect. These results indicate that HKT1 ; 2 has the more significant role in Na + homeostasis and salinity tolerance in tomato. Abstract : In this study, by using different transgenic lines derived from two near‐isogenic lines differing in terms of their HKT1;1/HKT1;2 gene allele (from S. lycopersicum or S. cheesmaniae ), in which all allelic variants were silenced by stable transformation, we found that the Na + transporter‐encoding gene HKT1;2 functionally underlies the major QTL lkc7.1 controlling shoot Na + /K + homeostasis and plays the most significant role in tomato salt tolerance.